Maternal near miss as a predictor of adverse perinatal outcomes: findings from a prospective cohort study in southwestern Uganda - Mark Jjuuko; Henry Mark Lugobe; Richard Migisha; David Collins Agaba; Leevan Tibaijuka; Musa Kayondo; Joseph Ngonzi; Paul Kato Kalyebara; Hamson Kanyesigye (BMC, 2024)
Abstract Background Despite efforts, Uganda has not met the World Health Organization target of < 12 newborn deaths per 1,000 live births. Severe maternal morbidity or 'near miss' is a major contributor to adverse perinatal outcomes, particularly in low-resource settings. However, the specific impact of maternal near miss on perinatal outcomes in Uganda remains insufficiently investigated. We examined the association between maternal near miss and adverse perinatal outcomes at Mbarara Regional Referral Hospital (MRRH) in southwestern Uganda. Methods We conducted a prospective cohort study among women admitted for delivery at MRRH's maternity ward from April 2022 to August 2022. We included mothers at ≥ 28 weeks of gestation with singleton pregnancies, while intrauterine fetal death cases were excluded. For the near-miss group, we consecutively included mothers with any one of the following: antepartum hemorrhage with shock, uterine rupture, hypertensive disorders, coma, and cardiac arrest; those without these complications constituted the non-near-miss group. We followed the mothers until delivery, and their infants until seven days postpartum or death. Adverse perinatal outcomes considered were low birth weight (< 2,500 g), low Apgar score (< 7 at five minutes), intrapartum stillbirths, early neonatal death, or admission to neonatal intensive care unit. Multivariable log-binomial regression was used to determine predictors of adverse perinatal outcomes. Results We enrolled 220 participants (55 maternal near misses and 165 non-near misses) with a mean age of 27 ± 5.8 years. Most of the near misses were pregnancies with hypertensive disorders (49%). Maternal near misses had a four-fold (adjusted risk ratio [aRR] = 4.02, 95% CI: 2.32-6.98) increased risk of adverse perinatal outcomes compared to non-near misses. Other predictors of adverse perinatal outcomes were primigravidity (aRR = 1.53, 95%CI: 1.01-2.31), and gestational age < 34 weeks (aRR = 1.81, 95%CI: 1.19-2.77). Conclusion Maternal near misses, primigravidity, and preterm pregnancies were independent predictors of adverse perinatal outcomes in this study. We recommend implementing maternal near-miss surveillance as an integral component of comprehensive perinatal care protocols, to improve perinatal outcomes in Uganda and similar low-resource settings. Targeted interventions, including specialized care for women with maternal near misses, particularly primigravidas and those with preterm pregnancies, could mitigate the burden of adverse perinatal outcomes.